Wounds to the dorsal carpus (coronation injury) in horses: Treatment, complications and survival. (30th June 2016) - Butz, N.; Dreyfus, A.; Fürst, A. E.; Bischofberger, A. S.
Summary: Studies evaluating complications, treatment and survival following wounds to the dorsal carpus (coronation injuries), despite being frequent injuries in equine practice, are lacking. The aim was to describe clinical features and identify risk factors associated with short‐ and long‐term outcomes following coronation injury in horses. Clinical data were obtained for horses undergoing treatment of unilateral or bilateral coronation injuries in a single hospital population. Descriptive data were generated for the clinical variables. Multivariable linear or logistic regression analyses was used to generate six models with short‐term outcomes defined as hospitalisation time and hospital survival; and long‐term outcomes (>6 months) defined as coronation specific mortality, sound and return to intended use, increased post‐injury stumbling and recurrence of coronation injury. One hundred and thirty‐eight horses were included. In 15.9% an extensor tendon and in 17.4% a carpal joint was involved. The prognosis for hospital survival was 97.8% and the long‐term coronation specific mortality risk was 4.3%. 87.5% were sound and returned to intended use. Risk factors for prolonged hospitalisation time were extensor tendon involvement (4.2 days), carpal joint involvement (3.8 days) and complications (skin necrosis [9.5 days] and local infection [3.2 days]. Coronation injuries reccurred in 8.8% and 20% had evidence of increased post‐injury stumbling. Administration of intra‐articular antimicrobials (7.8 times) (likely reflecting injury severity grade) and bilateral coronation injury (6.7 times) increased the odds for increased post‐injury stumbling. This study has identified risk factors for increased hospitalisation time and post‐injury stumbling, which clinicians managing coronation injuries should be aware of.